2013
DOI: 10.1021/jm401395s
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of Orally Bioavailable 1H-Pyrrolo[3,2-c]pyridine Inhibitors of Mitotic Kinase Monopolar Spindle 1 (MPS1)

Abstract: The protein kinase MPS1 is a crucial component of the spindle assembly checkpoint signal and is aberrantly overexpressed in many human cancers. MPS1 is one of the top 25 genes overexpressed in tumors with chromosomal instability and aneuploidy. PTEN-deficient breast tumor cells are particularly dependent upon MPS1 for their survival, making it a target of significant interest in oncology. We report the discovery and optimization of potent and selective MPS1 inhibitors based on the 1H-pyrrolo[3,2-c]pyridine sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 48 publications
3
85
0
Order By: Relevance
“…These assays are highly specific for Mps1, but hard to quantify. Another more recently demonstrated way of measuring Mps1 kinase activity is a mobility shift assay described by Naud et al [5]: phosphorylated and non-phosphorylated peptides are separated by electrophoresis based on their charges [14]. This mobility shift assay has been compared with a radiometric assay and found to be more robust [21].…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is mentioning
confidence: 99%
See 1 more Smart Citation
“…These assays are highly specific for Mps1, but hard to quantify. Another more recently demonstrated way of measuring Mps1 kinase activity is a mobility shift assay described by Naud et al [5]: phosphorylated and non-phosphorylated peptides are separated by electrophoresis based on their charges [14]. This mobility shift assay has been compared with a radiometric assay and found to be more robust [21].…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is mentioning
confidence: 99%
“…Due to its importance for the viability of tumor cells, Mps1 kinase has become a potential target for cancer treatment [2]. Over the past years, several dozens of small compounds have been developed to inhibit the Mps1 kinase activity [2][3][4][5][6][7]. Recently, NMS-P715 has been described to suppress the growth of medulloblastoma cells, a common malignant brain tumor in children [8].…”
Section: Introductionmentioning
confidence: 99%
“…Naud et al recently identified a series of 1H-Pyrrolo[3,2-c]pyridine derivatives as inhibitors of MPS1 through structure-based drug design, and obtained a crystal structure of MPS1with one inhibitor (T2), N-(3,4-dimethoxyphenyl)-2-(1H-pyrazol-4-yl)-1H-pyrrolo[3,2-c] pyridin-6-amine (PDB code: 4C4E) [36]. Here the 1H-pyrrolo[3,2-c]pyridin-6-amine moiety of T2 was defined as the core scaffold (Table 4).…”
Section: Retrospective Case Studiesmentioning
confidence: 99%
“…An overlay of the structure of Mps1 in complex with NMS-P715 bound, 12 with Mps1 bound to ATP 30 and a recent structure in which the K553/E571 catalytic pair has a more catalytically competent conformation, 39 shows structural variability particularly in the area around Y568, neighboring the mutated I598. As Mps1 inhibitors exert (part of) their effect through interfering with the K553/E571 catalytic pair, 30 it is not unlikely that the I598F mutation may limit Y568 flexibility, Figure 4.…”
Section: Mps1 Inhibitors As Potential Anticancer Therapy Reagentsmentioning
confidence: 99%
“…12 NMS-P715 is shown in yellow, the wild-type residues in grey, and mutated residues in coral. 12 (grey), with the crystal structures of an ATP bound 30 (green) and a pyrrolopyridine inhibitor 39 (blue). Only one main chain is shown for clarity.…”
Section: Mps1 Inhibitors As Potential Anticancer Therapy Reagentsmentioning
confidence: 99%